Degradasi Vegetasi Hutan Konservasi Danau Pulau Besar Danau Bawah Kabupaten Siak Provinsi Riau - Pramono, Tri Handro; Amin, Bintal; Syafriadiman, Syafriadiman; Mahatma, Radith (Dinamika Lingkungan Indonesia, 2015)
Wildlife Sanctuary of Danau Pulau Besar Danau Bawah is surrounded by a forestconservation area of industrial timber estates and villages inhabited by indigenous peopleswhere their lives are very dependent on the forest. The consequence of these conditions is thatforest degradation is quite serious as the encroachment of trees and forest conversionpractices to agriculture and plantations. This study aims to gain estimation on forestencroachment and total loss of trees resulting in a decline in floristic diversity in this region.Data collection on forest encroachment map using satellite imagery analysis was done byusing Supervised Classification technique. The area assessed is conservation forest areaswhich has been encroached upon or degraded areas. Vegetation data were collected by usingthe plot method that illustrates the potential, type, density values, dominance of vegetationand its importance value index. The results of extensive analysis of vegetation encroachmentillustrated the potential value of forest degradation rate. Conservation forests area wasdegraded up to± 2339.73 ha or 8.29% of the total area, while the estimated loss due to theencroachment of trees during the period 1998 to 2012 reached 550,819.24 m3 or equal to39,344.23 m3 trees per year, or 3278.69 m3 per month and 109.29 m3 per day.